Review: Current trends in coral transplantation â€“ an approach to preserve biodiversity - MOHAMMED SHOKRY AHMED AMMAR; FAHMY EL-GAMMAL; MOHAMMED NASSAR; AISHA BELAL; WAHID FARAG; GAMAL EL-MESIRY; KHALED EL-HADDAD; ABDELNABY ORABI; ALI ABDELREHEEM; AMGAD SHAABAN (Biodiversitas Journal of Biological Diversity, 2013)
Ammar MSA,El-Gammal F, Nassar M, Belal A, Farag W, El-Mesiry G, El-Haddad K, Orabi A, Abdelreheem A, Shaaban A. 2013.Â Review: Current trends in coral transplantation â€“ an approach to preserve biodiversity. Biodiversitas 14: 43-53. The increasing rates ofÂ coral mortality associated with the rise in stress factors and the lack of adequate recovery worldwide have urged recent calls for actionsÂ by the scientific, conservation, and reef management communities. This work reviews the current trends in coral transplantation.Â Transplantation of coral colonies or fragments, whether from aqua-, mariculture or harvesting from a healthy colony, has been the mostÂ frequently recommended action for increasing coral abundance on damaged or degraded reefs and for conserving listed or â€œat-riskâ€Â species. Phytoplanktons are important for providing transplanted corals with complex organic compounds through photosynthesis.Â Artificial surfaces like concrete blocks, wrecks or other purpose-designed structures can be introduced for larval settlement. NewÂ surfaces can also be created through electrolysis. Molecular biological tools can be used to select sites for rehabilitation by asexualÂ recruits. Surface chemistry and possible inputs of toxic leachate from artificial substrates are considered as important factors affectingÂ natural recruitment. Transplants should be carefully maintained, revisited and reattached at least weekly in the first month and at leastÂ fortnightly in the next three months. Studies on survivorship and the reproductive ability of transplanted coral fragments are importantÂ for coral reef restoration. A coral nursery may be considered as a pool for local species that supplies reef-managers with unlimited coralÂ colonies for sustainable management. Transplanting corals for making artificial reefs can be useful for increasing biodiversity, providingÂ tourist diving, fishing and surfing; creating new artisanal and commercial fishing opportunities, colonizing structures by fishes andÂ invertebrates,Â aving large corals during the construction of a Liquified Natural Gas Plant.